Reliability and availability assessment of transmission overhead line protection system using reliability block diagram - Ridwan M.I.; Yen K.L.; Musa I.A.; Yunus B. (2023)
Protection system in a power system domain plays a vital role as watchmen to safe guard power system apparatus in the event of faults. The integrity and effectiveness of these watchmen is heavily dependent on the reliability of the components that makes up the system. One of the main components in a protection system is protective relays that provides decision making element for correct protection and fault clearing operations. Failure of the protection devices may reduce the reliability of the power system protection that will impact the overall performance of the power system. Hence it is imperative for power utilities, such as Tenaga Nasional Berhad (TNB) to assess the reliability of protective relays to assure it will perform its intended function without failure. This paper will discuss the application of reliability block diagram (RBD) to assess the reliability and availability of a typical 132kV transmission overhead line protection system using historical failure data of protective relays. 2010 IEEE.